The Qualities and Techniques of English Translation of the Functional Texts at Railway Stations - Muhammad Zainal Muttaqien; Robith Khoiril Umam; Arkin Haris; Dona Aji Karunia Putra (Fakultas Komunikasi, Sastra, dan Bahasa, 2026)
Informational texts in public spaces, like railway station, are often provided in English language to serve international visitors. The English version is commonly the result of translation from the original in local language. However, sometimes, a number of mistakes are found in the target texts that can lead to confusion or misunderstanding to the readers. This descriptive qualitative research aimed at measuring the quality of English informational texts provided at the railway stations. For collecting the textual data, a documentation technique was applied. The selected data were then processed through interactive model of data analysis proposed by Miles and Huberman (1994). For measuring the translation quality of the informational texts, the researcher uses the model of translation quality assessment developed by Nababan, Nuraeni, and Sumardiono (2012) which considering accuracy, acceptability, and readabilty as the parameters for scoring. Meanwhile, for the purpose of analyzing the mistakes in the target texts, it used Molina and Albir’s (2002) theory of translation techniques. The results show that, overall, the English translation is considered having good quality as it reaches a total score of 2.70 out of maximum 3 points. Meanwhile, from the total 110 times of use, 11 out of 18 translation techniques were applied by the translator. Borrowing becomes the most frequent technique used, in contrast with description as the rarest. To some extent, the quality of translation is influenced by the choice of translation techniques in the process of translation.